Safety Technology Risks and Countermeasures in the Intelligent Construction of Coal Mines - Jinyan Bai; Dezhi Zheng; Chen Jia (Geofluids)
At present, China’s intelligent coal mine construction is still in the primary development stage. The integrated development of a new generation of information and communication technology and the coal industry is accelerating, and this industry’s intelligent green transformation and upgrading is being promoted. With the continuous acceleration of China’s intelligent coal mine construction and the continuous improvement in the degree of coal mine intelligence, system compatibility, information acquisition, and intelligent research have raised awareness of new mining safety risks. Based on the analysis of the process of China’s intelligent construction, this paper describes the safety management and control risks and the technical challenges faced by China’s intelligent coal mine construction in terms of norms and standards, data acquisition, subsystem and terminal sensors, multisystem integration, safety risk management, and control ability. It is important to make full use of the collaborative advantages of intelligent scientific and technological coal mine resources. Technological innovation and intelligent equipment safety access verification need to be supported, so as to promote the intelligent and high-quality development of coal mines.